2020
DOI: 10.1177/2055217320975185
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity monitoring to assess disability progression in multiple sclerosis

Abstract: Background Clinical outcome measurement in multiple sclerosis (MS) usually requires a physical visit. Remote activity monitoring (RAM) using wearable technology provides a rational alternative, especially desirable when distance is involved or in a pandemic setting. Objective To validate RAM in progressive MS using (1) traditional psychometric methods (2) brain atrophy. Methods 56 people with progressive MS participated in a longitudinal study over 2.5 years. An arm-worn RAM device measured activity over six d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…This is in line with evidence from preclinical animal models and human studies that support the beneficial effect of aerobic exercise on the hippocampus region [70,71]. Although these findings are important and provide a clear rationale to determine effects of changes in physical activity on clinical measures of disease progression and activity longitudinally, it remains elusive why only a limited number of studies integrated follow-up measurements [49,53,57,72]. A pilot study of Bahmani et al [49] showed that vigorous physical activity, assessed by questionnaire, decreased during the first 2 years of disease, although not being associated with changes in the EDSS.…”
Section: Physical Activitysupporting
confidence: 71%
“…This is in line with evidence from preclinical animal models and human studies that support the beneficial effect of aerobic exercise on the hippocampus region [70,71]. Although these findings are important and provide a clear rationale to determine effects of changes in physical activity on clinical measures of disease progression and activity longitudinally, it remains elusive why only a limited number of studies integrated follow-up measurements [49,53,57,72]. A pilot study of Bahmani et al [49] showed that vigorous physical activity, assessed by questionnaire, decreased during the first 2 years of disease, although not being associated with changes in the EDSS.…”
Section: Physical Activitysupporting
confidence: 71%
“…These participants had a mean age ranging from 10.1 to 74.4 years and 56.42% (1380/2446) were female. Of the 30 studies, 2 (7%) targeted a pediatric population (aged<18 years [ 30 , 31 ], 21 (70%) studied adults with a mean age between 40 and 65 years [ 32 - 49 , 54 , 55 , 61 ], and 6 (20%) evaluated individuals aged >65 years [ 50 - 52 , 56 - 58 ]. Approximately 50% (15/30) of studies recruited participants from specialist tertiary clinics, with the remaining 50% (15/30) recruiting participants in the community (eg, primary care settings and rehabilitation centers).…”
Section: Resultsmentioning
confidence: 99%
“…Our findings built on a small body of prior work that explored the feasibility of passive sensing in people with MS and preliminary correlations between passively sensed behaviors and MS outcomes. For example, Newland et al [ 26 ] explored real-time depth sensors at home to identify gait disturbance and falls in 21 patients with MS. Other studies reported correlations between passively sensed physical activity and disability worsening in people with MS [ 27 , 62 , 63 ]. Chitnis et al [ 28 ] examined the gait, mobility, and sleep of 25 people with MS over 8 weeks using sensors mounted on their wrist, ankle, and sternum, and reported correlations among gait-related features (eg, turn angle and maximum angular velocity), sleep and activity, and disability outcomes.…”
Section: Discussionmentioning
confidence: 99%